Análise de oportunidades e desafios da gestão de resíduos sólidos no município de Simão Dias (SE) - Almeida, Camila Couto de (2023)
In Brazil, total access to basic sanitation is a challenge, where the rates of care and deficit vary according to the income, region, and isolation of the areas and size of the municipality. The absence of adequate management of solid waste results in environmental, social, and economic impacts. Considering that it is the municipal competence for the integrated management of solid waste generated in the respective areas observed in small municipalities (municipalities with up to 50,000 inhabitants) for proper management is the lack of financial resources and professionals with technical capacity. About 89% of Brazilian municipalities are within this category. These challenges are aggravated by factors in rural areas, a common reality in small municipalities. In Simão Dias (SE), a city with about 40,000 inhabitants, located inland of Sergipe and with strong rural influence, there is no legal compliance to solid waste management properly. Thus, the general objective of the research was to analyze the opportunities and challenges of municipal solid waste management in the municipality of Simão Dias (SE). For this, the accomplished steps were: a) a literature review of solid waste in the nation and recommendations in an international and national context; b) a characterization of the solid waste in Simão Dias through local visitation (Article 1) and c) use of strategic evaluation tools (SWOT and 5W2H) to solid waste management (Article 2). The main challenges were the absence of public policies for appropriate management, lack of knowledge about the origin and quantification of waste disposal, absence of adequate segregation in the generating source, and inefficiency of actions for selective collection. The performance of the current cooperative and the municipal participation in a consortium stood out as opportunities. Regarding the identified challenges, 11 proposals for actions were detailed, such as the construction of landfill, an elaboration of the municipal plan for integrated solid waste management and environmental education initiatives for segregation of solid waste properly in the city.